The role of marketing capability in linking CSR to corporate financial performance: When CSR gives positive signals to stakeholders. (8th April 2019) - Yim, Sean; Bae, Young Han; Lim, Hyunwoo; Kwon, JaeHwan
Abstract : Purpose: The authors use signaling theory in proposing a conceptual framework that simultaneously incorporates both the mediating effects of corporate reputation (CR) and the moderating effects of marketing capability (MC) into the corporate social responsibility (CSR)–corporate financial performance (CFP) link and theorize a single moderated mediation model. The empirical results of the research confirm the theorized moderated mediation model among the four variables, where a firm's CR plays a mediating role in the relationship between CSR and CFP, and a firm's MC moderates the effect of CSR on CR exclusively in the first link. Both theoretical and practical implications of the moderated mediation model are discussed. Design/methodology/approach: This study uses structural equation model estimations with the relevant secondary datasets collected from publicly available databases. Findings: The empirical results confirm the theorized moderated mediation model in the conceptual framework that uses signaling theory. Specifically, the results identify the moderating role of MC in only the CSR- CR link (but not in the CR and CFP link), such that CR plays a moderated mediation role in the CSR–CFP link. Research limitations/implications: The current research is not without limitations. These limitations mainly stem from data sets used in the empirical analyses. More details are discussed in the limitations and future research directions section. Practical implications: The empirical findings suggest that a firm needs to develop a consolidated CSR-marketing program, simultaneously satisfying stakeholders' needs for both the firm's socially desirable business practices and value-creating marketing programs to increase its CR, which will, in turn, lead to better profitability for the firm. Originality/value: To the best of the authors' knowledge, the current research is the first to use signaling theory in building a conceptual framework that theorizes a moderated mediation model regarding the simultaneous effects of CR and MC on the relationship between CSR and CFP and to empirically test this conceptual framework of the single moderated mediation model. By doing so, the current research clarifies an unanswered question in the literature of whether the underlying mechanism in the CSR–CFP link is based on a mediated moderation or moderated mediation of CR and MC.